Epidemiological profile of patients with Covid-19 undergoing extracorporeal membrane oxygenation in the period 2020-2022 (Research, Society and Development, 2022)
Covid-19 disease tends to be more incident and extreme in men, which is defined by each morbid and behavioral explanations - in females, the occurrence of diseases that lead to worsening occurrences decreases considerably when compared to males, due to to lifestyle and health habits. The study aims to trace the epidemiological profile of patients who used extracorporeal membrane oxygenation during the coronavirus pandemic between 2020 and 2022. This is an integrative literature review carried out through the Scientific Electronic Library Online (SciELO) databases, Latin American and Caribbean Literature on Health Sciences (LILACS) and Medical Literature Analysis and Retrieval System Online (MEDLINE), through the following Health Sciences Descriptors (DeCS): “coronavirus”, “extracorporeal membrane oxygenation” and “ epidemiology". Combined with each other by the Boolean operator AND. As inclusion criteria: articles available in full, in Portuguese, Spanish and English, that addressed the theme, between 2020 and 2022. As exclusion criteria: articles that did not cover the theme and repeated studies in the databases. 164 articles were found, after the combined search of descriptors and Boolean operators, 6 articles were selected to compose the final sample, as shown in the table below. Thus, the profile of patients admitted to a referral hospital for coronavirus, for the most part, was in line with different research on Covid-19 in Brazil and in the world: men, over 50 years old with presence of comorbidities, being the most prevalent diabetes and hypertension.